Perceptions of Australasian emergency department staff of the impact of alcohol-related presentations - Egerton-Warburton, Diana; Gosbell, A.; Wadsworth, A.; Moore, K.; Richardson, D.; Fatovich, D. (Australasian Medical Publishing, 2016)
Objectives: To survey emergency department (ED) clinical staff about their perceptions of alcohol-related presentations. Design, setting and participants: A mixed methods online survey of ED clinicians in Australia and New Zealand, conducted from 30 May to 7 July 2014. Main outcome measures: The frequency of aggression from alcoholaffected patients or their carers experienced by ED staff; the perceived impact of alcohol-related presentations on ED function, waiting times, other patients and staff. Results: In total, 2002 ED clinical staff completed the survey, including 904 ED nurses (45.2%) and 1016 ED doctors (50.7%). Alcohol-related verbal aggression from patients had been experienced in the past 12 months by 97.9% of respondents, and physical aggression by 92.2%. ED nurses were the group most likely to have felt unsafe because of the behaviour of these patients (92% reported such feelings). Alcohol-related presentations were perceived to negatively or very negatively affect waiting times (noted by 85.5% of respondents), other patients in the waiting room (94.4%), and the care of other patients (88.3%). Alcohol-affected patients were perceived to have a negative or very negative impact on staff workload (94.2%), wellbeing (74.1%) and job satisfaction (80.9%). Conclusions: Verbal and physical aggression by alcohol-affected patients is commonly experienced by ED clinical staff. This has a negative impact on the care of other patients, as well as on staff wellbeing. Managers of health services must ensure a safe environment for staff and patients. More importantly, a comprehensive public health approach to changing the prevailing culture that tolerates alcohol-induced unacceptable behaviour is required.